Designing a highly immersive interactive environment: the virtual mine - Soares, L. P.; Pires, F. L.; Varela, R. N.; Bastos, R.; Carvalho, N.; Gaspar, F.; Dias, M. S. (Computer Graphics Forum, 2010)
To achieve a full-scale simulation of a pyrite mine, a highly immersive environment becomes necessary and this research has led to a complex system enabling users to walk through a virtual mine in real time, presenting all the behaviours present in such environment. Some of the problems encountered are the tunnels behaviours, including highly contrasted images due to the presence of the head light, narrow paths, elevators, sound reverberation and tunnels texture shades. The use of immersive virtual reality enables the generation of high-quality simulations, because it is possible to control several feedback mechanisms such as the degree of luminance of produced imagery and spatial sound. In this research, a projection infrastructure and tracking system were specified and developed, aiming at producing the best results for this kind of simulation. To achieve our purposes, distributed algorithms were developed to run in a cluster solution that drives a four-sided CAVE-like environment. The complete production pipeline is presented, ranging from the developed authoring techniques, enabling fast production of new content for the simulation, to the tracking techniques produced for the improvement of the interaction.